Systemic and meta-analyses of diabetic retinopathy and its care-related predictors after diabetic mellitus treatment initiation in Ethiopia - Aboma Motuma; Abdi Birhanu; Lemma Demissie Regassa; Sina Tolera; Alemayehu Deressa; Usmael Jibro; Mulugeta Gamachu; Moti Tolera; Adera Debella; Bikila Balis; Addis Eyeberu; Fethia Mohammed; et al. (Endocrine and Metabolic Science)
Background: Diabetic retinopathy (DR) is a major complication of diabetes mellitus (DM) that affects the blood vessels of the retina and cause vision loss and blindness. DR is a major public health problem worldwide, especially in low-and middle-income countries where access to screening and treatment is limited. Although Ethiopia has implemented a strategic plan targeting DM care improvement to reduce complications from 2020 to 2025, retinopathy is a severe complication among DM patients. Therefore, this study aimed to assess diabetic retinopathy among DM patients after treatment initiation in Ethiopia from 2020/2021 to 2024/2025 after the strategy was implemented. Method: Using the preferred reporting items for systematic reviews and meta-analysis guidelines, we systematically reviewed and meta-analyzed articles from Scholar, PubMed, Excerpta Medical Database (EMBASE), Cochrane Library, and MESH Medline. The data were extracted using Microsoft Excel and analyzed using STATA version 17. The pooled risk of new diabetic retinopathy among diabetes patients who started DM treatment was estimated. To minimize the effect of heterogeneity, subgroup analysis was performed by geographical region and year of publication (between 2020 and 2023). Publication bias was detected using a funnel plot, with P < 0.05 assumed to indicate potential publication bias. The I2 test was used to assess the heterogeneity of the studies. Results: The pooled risk of diabetic retinopathy among treated DM patients was 25.43% (95% CI: 18.1, 32.7) from 2020 to 2023. The incidence of DR was 28.6% in the South Nation, Nationalities, and People (SNNPs) region, followed by Oromia (31.35%) and Amhara (22.93%). Care-related factors such as receiving a combination of DM medication (AOR=0.62, 95% CI: 0.47–0.82, n=3), having good glycemic control (AOR=0.24, 95% CI; 0.17–0.33, n=4), and comorbidities with hypertension (AOR=1.39, 95% CI; 1.17–1.87, n=4) were predictors of diabetic retinopathy development among DM patients at follow-up. Conclusion: Even if the studies could not be combined due to high heterogeneity, they demonstrated that diabetic complications, particularly DR, are still high after starting treatment among DM patients in Ethiopia. Care-related factors such as treatment modalities, glycemic control levels, and comorbidities with hypertension should be appropriately screened and managed to reduce the burden of DR among DM patients receiving follow-up care in Ethiopia. Moreover, Ethiopia should evaluate the already set plan implementation status to achieve the target set by 2025.